An Evaluation of the Efficacy of Two Different Types of Plastic Waste Materials to Enhance the Geotechnical Characteristics of Soft Clay Soils - Rania Hayder Fadhil; Balqees Abdulwahid Ahmed (Journal of Engineering)
Plastic waste materials are constantly increasing around the world as a result of the growing human consumption of these materials day by day, with no actual solutions to get rid of them without causing harm to the environment or the health of living organisms. Therefore, in this research, two types of plastic waste materials are utilized to enhance soft clay soil: polyethylene terephthalate (PET) and nylon (N), in percentages of (1, 1.5, 2, 2.5)% from dry soil weight, to enhance the clay soft soils properties, which are characterized by their excessive compressibility, low bearing capacity, and low shear strength. This study is carried out by conducting laboratory tests before and after the addition. These tests included the unconfined compressive strength (UCS) test, and the other test was the consolidation test. The results revealed a notable rise in the cohesion value (C) when using polyethylene terephthalate (PET), when the enhancement reached 246.42% with 2.5%, while the maximum improvement percent with nylon was 25% with 1.5%. On the other hand, when applied at a rate of 2%, nylon trash was more effective than plastic water bottles (PET) in reducing the compression index (Cc), dropping from 0.26 to 0.15.